Edukasi Cara Sikat Gigi Pada Ibu Siswa TK Perwanida Kotawaringin Barat Kalimantan Tengah - Shesanthi Citrariana; Tri Megawati (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Dental health is part of overall health. Mother's level of knowledge has an important role in maintaining dental health in her child. Preschoolers are children aged between 4-6 years which is called the "golden age". So that in the preschool period mothers should have taught children how to brush their teeth properly. This service aims to provide education and increase mother's knowledge about brushing teeth to students of Perwanida Kindergarten, West Kotawaringin Regency, Central Kalimantan. This service is carried out by providing education to 50 mothers through speeches using visual aids about proper tooth brushing procedures. Measuring the level of knowledge was carried out using pretest and posttest questionnaires. Mother's knowledge level data were analyzed using MS.Excel and then translated into Good, Adequate, and Poor knowledge level categories. The results of this activity showed that there was an increase in mother's knowledge in the Good category from 53% to 74% and a decrease in mother's knowledge in the Enough category from 45% to 26% and in the Less category 2% to 0%. Based on the results of the education, it can be concluded that Education on the Use of Toothbrushes for Mothers of Perwanida Kindergarten students in West Kotawaringin, Central Kalimantan is said to be successful with an increase in the Good knowledge category. It is recommended that health workers can improve health promotion on how to brush their teeth properly in order to reduce the incidence of dental disease in children.